Changes in expiratory flow limitation during exercise from pre- to post-puberty - Emerson, Sam R. (Kansas State University, 2014)
Expiratory flow limitation (EFL) during exercise can limit exercise tolerance. We have recently reported a high prevalence of EFL independent of sex in prepubescent children (Swain et al. 2010) that greatly exceeds that reported in adults. It is unknown how maturation and growth from pre- to post-puberty affects pulmonary function, specifically EFL, during exercise. The purpose of this longitudinal study was to investigate the changes in cardiopulmonary function from pre- to post-puberty in boys and girls. We hypothesized that EFL prevalence would decrease from pre- to post-puberty (with boys exhibiting a greater decrease than girls) and that the decrement could be explained by an increase in pulmonary function and a decrease in VE/VCO2. Twenty-one children (ages 12-16 yrs; 11 boys, 10 girls) were recruited from 40 prepubescent children who completed testing in our laboratory ~5 years ago. Subjects completed pulmonary function tests before and after an incremental exercise test to exhaustion (VO2max) on a cycle ergometer. EFL was determined using the percent tidal volume (VT) overlap method. Nineteen of the 21 subjects (10 boys, 9 girls; 90%) exhibited EFL pre-puberty, while only 7 of the 21 subjects (5 boys, 2 girls; 33%) exhibited EFL post-puberty. Of the subjects who experienced EFL post-puberty, all had experienced EFL pre-puberty. Boys had a significantly greater vital capacity (VC) than girls both pre- (~15%) and post-puberty (B: 4.73 ± 0.53; G: 3.80 ± 0.29 L). Maximal aerobic capacity (VO2max) significantly increased (~110% in girls and ~120% in boys) from pre- to post-puberty and was greater (p<0.05) in boys post-puberty (B: 2.76 ± 0.43; G: 1.94 ± 0.35 L/min). VE/VCO2 also significantly decreased (~13%) in both boys and girls. Post-puberty subjects regulated tidal breathing at higher lung volumes (greater ERV/FVC and lower IRV/FVC) during exercise compared to pre-puberty. None of the subjects experienced significant arterial desaturation pre-puberty or post-puberty. Our findings suggest that the prevalence of EFL declines as children mature from pre- to post-puberty, likely due to increases in lung size, decreases in VE/VCO2, and/or changes in breathing mechanics that are greater than increases in maximal ventilation that occur with increased pulmonary gas exchange.
Keywords: Flow limitation; Exercise; Puberty; Sex differences; Kinesiology (0575)